Analisis Strategi Pengembangan Bisnis Melalui Matriks SWOT pada Startup MakananHalal.id - Ratih Puspita Sari; Iis Mariam; Mawarta Onida Sinaga (Research Center and Case Clearing House PPM School of Management, 2021)
The purpose of this study was to find alternative strategies used by FoodHalal.id startups in developing their business. The problems regarding the analysis of internal factors, external factors, and SWOT matrix. The methodology used is descriptive qualitative with in-depth interviews, informants are CEOs and employees of MakanHalal.id, restaurant owners who collaborate with MakanHalal.id. The results of research are grouped into 4 categories, namely: (1). Alternative SO Strategy expands the halal food network in all areas of DKI Jakarta using social media to promote Halal Food, join as driver partners. (2) Alternative WO strategy by creating social media accounts with interesting content to increase traffic. holding live quizzes or giveaways on social media while the system is off, expanding the coverage area and delivery distance in DKI Jakarta area can access Halal.id Food, (3) Alternative ST Strategy by collaborating with businessmen to pre-order on the FoodHalal.id application, holding promotions, marketing that Halal.id is more flexible than other applications, (4) Alternative WT strategy: establishing cooperation with restaurant businesses that have not yet opened their own online delivery, increasing the delivery distance of more than 25km to be able to compete with competing applications. Further research focus on digital marketing strategies for halal food businesses.